Benzoyl Peroxide Promoted Radical ortho‐Alkylation of Nitrogen Heteroaromatics with Simple Alkanes and Alcohols. Issue 9 (12th February 2015) - Fang, Lei; Chen, Liangshun; Yu, Jianjun; Wang, Limin
Abstract: A catalytic amount of benzoyl peroxide (BPO)‐initiated cross‐dehydrogenative coupling reaction of N ‐iminopyridine ylides with simple alkanes and alcohols leads to the corresponding 2‐alkylpyridines with high regioselectivity in moderate to good yields without an additional reduction step to remove the activated group. Abstract : A catalytic amount of benzoyl peroxide (BPO)‐initiated cross‐dehydrogenative coupling reaction of N ‐iminopyridine ylides with simple alkanes and alcohols has been developed. The strategy allowed convenient access to various 2‐alkylpyridines in moderate to good yields without an additional reduction step to remove the activated group.